The Effects of Learning Interest and the Use of Animated Video Media on Fourth Grade Elementary School Students’ Science Learning Outcomes - Ilaturizki, Mahni; Darmiany; Ida Ermiana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study was motivated by the low learning interest and science learning outcomes of fourth-grade elementary school students in ecosystem and food web topics, which were attributed to the use of traditional teaching methods that were less engaging. The study aimed to analyze the effects of learning interest and the use of animated video media on students’ science learning outcomes. This research employed a quantitative approach with an ex post facto correlational design. The population consisted of all fourth-grade students at SDN 26 Mataram (29 students), who were selected as the sample through total sampling. The research instruments included Likert-scale questionnaires to measure learning interest and the use of animated video media, as well as a posttest to assess learning outcomes. Data were analyzed using Pearson’s product–moment correlation, multiple regression analysis, t-tests, and F-tests. The results indicated that 60% of students had a high level of learning interest, with an average learning outcome score of 82, and a significant relationship was found between learning interest and learning outcomes (p < 0.05). The study concludes that animated video media are effective in simultaneously enhancing students’ learning interest and science learning outcomes.